2019
DOI: 10.1186/s13059-019-1921-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct epigenetic features of tumor-reactive CD8+ T cells in colorectal cancer patients revealed by genome-wide DNA methylation analysis

Abstract: BackgroundTumor-reactive CD8+ tumor-infiltrating lymphocytes (TILs) represent a subtype of T cells that can recognize and destroy tumor specifically. Understanding the regulatory mechanism of tumor-reactive CD8+ T cells has important therapeutic implications. Yet the DNA methylation status of this T cell subtype has not been elucidated.ResultsIn this study, we segregate tumor-reactive and bystander CD8+ TILs, as well as naïve and effector memory CD8+ T cell subtypes as controls from colorectal cancer patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 58 publications
2
77
0
Order By: Relevance
“…44 Moreover, changes in global DNA methylation patterns of TILs influence CRC progression from onset to metastasis. 45 Herein, we found that T cell proliferation and differentiation-and cell cycle-related genes were significantly downregulated and chromatin-mediated epigenetic silencing pathways were upregulated in advanced stages of CRC, compared with early stages. These data suggest that chromatin-silencing plays an indispensable role in the progression of CRC.…”
Section: Discussionmentioning
confidence: 82%
“…44 Moreover, changes in global DNA methylation patterns of TILs influence CRC progression from onset to metastasis. 45 Herein, we found that T cell proliferation and differentiation-and cell cycle-related genes were significantly downregulated and chromatin-mediated epigenetic silencing pathways were upregulated in advanced stages of CRC, compared with early stages. These data suggest that chromatin-silencing plays an indispensable role in the progression of CRC.…”
Section: Discussionmentioning
confidence: 82%
“…CD8 + TILs become exhausted and lose their effector functions in the TME due to numerous factors, such as immunosuppressive mechanisms by tumor cells. Analyzing the transcriptome and methylome of CD8 + TILs in the TME of colorectal cancer simultaneously, Yang et al confirmed tumor-reactive TILs have an exhausted tissue-resident memory signature [ 117 ]. They showed tumor-reactive markers CD39 and CD103 of CD8 + TILs were demethylated and CD8 + TILs had an exhausted phenotype, including high expression of CTLA4, HAVCR2, LAYN, and TOX [ 117 , 118 ].…”
Section: Role Of Dna Methylation In Regulating T Cell Exhaustionmentioning
confidence: 99%
“…CD8 + T cells plays an important role of specifically recognising and killing tumour cells via releasing cytotoxic molecules in antitumour immune response, whereas only part of CD8 + tumour infiltrating lymphocytes (TILs) can recognise tumour-specific neoantigen and achieve targeted killing. Recently, increasing evidence has shown that CD39 is a marker of tumour-specific T cells, [13][14][15] though it was considered to be a biomarker of exhausted T cells in some studies. They found that CD39 + CD8 + T cells had stronger antitumour ability than CD39 − CD8 + T cells in six different malignant tumour types.…”
Section: How Might It Impact On Clinical Practice In the Foreseeable mentioning
confidence: 99%